First-Principles Calculations of Structural, Elastic and Electronic Properties of Tetragonal HfO2 under Pressure - 刘其军 刘正堂 冯丽萍 (Communications in theoretical physics, 2011)
Structural, elastic and electronic properties of tetragonal Hf02 at applied hydrostatic pressure up to 50 GPa have been investigated using the plane-wave ultrasoft pseudopotential technique based on the first-principles density- functional theory （DFT）. The calculated ground-state properties are in good agreement with previous theoretical and experimental data. Six independent elastic constants of tetragonal Hf02 have been calculated at zero pressure and high pressure. From the obtained elastic constants, the bulk, shear and Young＇s modulus, Poisson＇s coefficients, acoustic velocity and Debye temperature have been calculated at the applied pressure. Band structure shows that tetragonal Hf02 is an indirect band gap. The variation of the gap versus pressure is well fitted to a quadratic function.